A new method for estimating the prevalence of clonorchiasis in Korea: A proposal to replace arbitrary riverside sampling. Issue 13 (March 2017) - Jeong, Jin-Young; Lee, Jin Yong; Chung, Byung-Suk; Choi, Younghyun; Alley, Allison Baer; Kim, Hyun Joo
Abstract : Abstract: South Korea presently uses an arbitrary sampling method to monitor the prevalence of Clonorchis sinensis infection in the endemic areas of the country. However, the present method is not standardized and focuses primarily on individuals who reside nearest to the mainstream river. We propose a new sampling method that combines cluster sampling with proportionate quota sampling to ensure that the entire endemic area is accurately represented. We tested the new method in Okcheon-gun, South Korea, and determined that the C sinensis infection prevalence (8.9%) in 2013 was higher than that (6.9%) estimated in 2012 when the arbitrary method was used. Additionally, no difference was observed in the prevalence based on the distance from the riverside areas, including branches and creeks, between the areas <1 and >1 km away from the riversides. Therefore, health authorities should place equal emphasis on all regions within the endemic areas. Based on the findings, we recommend the following: the clonorchiasis prevalence rate must be measured using probability sampling, (clear guidelines on survey coverage should be provided to include the riverside areas and all areas nearby branch streams, and regional cohorts should be created for continuous monitoring of prevalence rates across the region.